Implementasi Paradigma Publish-Subscribe Untuk Menjalankan Event-Based Monitoring Pada Sistem Pengamatan Kandang Ternak - Adytya Tri Syahrul Alim; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Broiler chickens are one of the main needs of the community. Poultry production ranks at the top in meeting meat needs by contributing 70 percent of the total 3.5 million tons of meat production throughout Indonesia. The potential for fulfilling the needs of chicken meat has a high risk with high environmental temperatures due to global warming. The factors that cause crop failure due to climate change are the influence of weather conditions, cages and the environment caused by the chickens being susceptible to infection. So that we need a system that can monitor the conditions of the cage to adjust the condition of the chicken's body with the surrounding environment. The system that is made consists of 3 components, namely publisher, broker, subscriber. The first component is a series of DHT11 temperature and humidity sensors on the ESP8266 as a microcontroller and also as a WIFI module, coupled with a USB webcam camera to monitor conditions in the cage as a publisher. Then the Raspberry Pi microcomputer acts as a server as well as functions as a broker. Data transmission is carried out using the help of a wireless network and data processing is carried out in a local broker. From the research made, the test results obtained are as expected and obtained the system performance which refers to the average latency value below 1ms, namely 0.31 ms. Keywords: IoT, raspberry pi, temperature and humidity, MQTT, publish subscribe